Association of Novel Single Nucleotide Polymorphisms of Genes Involved in Cell Functions with Male Infertility: A Study of Male Cases in Northwest Iran - E Ghadirkhomi; A Angaji; M Khosravi; MR Mashayekhi (JRI, 2021)
Background: Infertility is a global health problem caused by various environmental and genetic factors. Male infertility accounts for 40–50% of all cases of infertility and approximately half of them are grouped as idiopathic with no definitive causes. Previous studies have suggested an association between some SNPs and infertility in men. In this study, an attempt was made to investigate the association of 7 different SNPs of 4 genes involved in common cell functions with male infertility. Methods: MTHFR rs1801131 (T>G), MTHFR rs2274976 (G>A), FASLG rs80358238 (A>G), FASLG rs12079514 (A>C), GSTM1 rs1192077068 (G>A), BRCA2 rs4987117(C>T), and BRCA2 rs11571833 (A>T) were genotyped in 120 infertile men with idiopathic azoospermia or severe oligospermia and 120 proven fertile controls using ARMS-PCR methods. Next, 30% of SNPs were regenotyped to confirm the results. Odds ratios (ORs) with 95% confidence intervals (CIs) were calculated using SPSS statistical software to evaluate the strength of association. The p˂0.05 were considered statistically significant. Results: Statistical analysis revealed significant association between MTHFR rs2274976 AA variant (OR: 10.00, CI: 3.203-31.225), FASLG rs12079514 AC variant (OR: 0.412, CI: 0.212-0.800), and BRCA2 rs11571833 TT variant OR: 6.233, CI: 3.211-12.101) with male infertility, but there was no significant difference between case and control groups in MTHFR rs1801131 (p= 0.111), GSTM1 rs1192077068 (p=0.272), BRCA2 rs4987117 (p=0.221), and FASLG rs80358238 (p=0.161). Conclusion: Our findings suggested that some novel polymorphisms including MTHFR rs2274976, FASLG rs12079514, and BRCA2 rs11571833 might be the possible predisposing risk factors for male infertility in cases with idiopathic azoospermia.